Estudos preliminares em taioba (Colocasia sp.) nas condições edafoclimáticas de Manaus () - Paiva, Waldelice Oliveira de; Weigei, Peter; Silva Filho, Danilo Fernandes da; Machado, Francisco Manoares (Acta Amazonica, 1981)
Preliminary observations are reported on the taro (Colocasia sp.) in Manaus, AM. The plants yielded the equivalent of 10.63 t/ha. Based on phenotipyc observations, the plants were classified for early maturing and yield. Significant differences were detected for the characters. The yield of tuber roots in class 4 (plants with original leaves), was the best, but slowest. Classes 1 and 2 (more than eight and one to seven new leaves respectively) did not produce as leanly as class 4, but are considered to be better in practice because of their early maturing. The character center corm weight showed a positive correlation with the yield of tuber roots in classes 1, 2 and 3. Thus screening for a bigger center corm will resulte in the formation of a more produtive cultivar.